Aging Society: Risk Factors, Injury Mechanisms, and Appropriate Exercise for Elderly - บุญแฝง, อรนิตย์; ริโก, นิภาพร; เจริญรัตน์, ชินภัทร; โยตา, วุฒิชัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Thailand is becoming a completely aged society, with seniors expected to comprise more than 28% of the total population by 2031. Age-related physiological deterioration affects all organ systems, including musculoskeletal, cardiovascular, neurological, and metabolic systems. The purpose of a literature review is to clarify the age-related mechanisms of changes, risk factors of injury, molecular and systemic repairing mechanisms, and exercise recommendations. The common injuries found in the elderly are hip fractures, traumatic brain injury, and compressed spinal fractures. The internal factors affecting these injuries are sarcopenia, osteoporosis, and impaired balance, whereas the external factors are the living environment, multiple drugs, and healthcare behavior. Moreover, the repairing mechanism is significantly declined with age due to stem cell degeneration, fibrogenesis, and a lack of molecular repairing mechanisms. Therefore, this article suggests an exercise regimen suitable for older adults, which consists of four main elements: aerobic, resistance, balance, and flexibility exercises. Regular exercise not only delays the physiological deterioration but also promotes mental health, reduces depression, and improves the quality of life in the elderly, comprehensively and sustainably.